Empreendedorismo social e economia criativa: uma aplicação em projetos de orquestras infantojuvenis - Duarte, Tatiane Lopes (2015)
The society we live in faces several conflicting situations. While the technology and innovation develop every day new products that promote significant progress in the conditions of human existence on the planet, frighteningly grows the gap between its availability and the possibilities of access to most humans inhabit it. In this context arises the movement of social inclusion through classical music provided by youth orchestra projects. The research problem that guided this research is: What are the organizational characteristics and the management ways of youth orchestras that promote their sustainability? Its general purpose is: To analyze the organizational characteristics and the management way of youth orchestras Projects that promote their sustainability, in the light of social entrepreneurship and the creative economy. The references focus on creative economy and social entrepreneurship. The object of investigation was the youth orchestra Projects and it was held an exploratory qualitative research. The studied projects were: Baccarelli Institute (Sao Paulo); Neojibá Program (Bahia); Youth Orchestra of Rio Grande do Sul (Porto Alegre); Orchestra Villa Lobos (Porto Alegre); Orchestrarium Program (Santa Maria). The research was structured in three stages (i) documentary; (ii) observation; and (iii) interviews. Data analysis was performed by text analysis, protocols and records analysis, content analysis and triangulation. The main evidence in relation to the projects is its central mission of social transformation in the context of the community where they are inserted.